Pembangunan Berbasis Lingkungan dalam Pandangan Islam Suatu Tinjauan Ekofeminisme - S, Agustina Dewi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
In the era of globalization, the existence of a country is seen from the quantity and quality of development, especially development that is physical and material. When this material development gets good grades, the dots on the non-physical development side will be covered explicitly or implicitly. Once the masculine parameters of development in this globalization era. Therefore, it is only natural when development on all fronts is finally nuanced masculine. Feminine values ​​become something that is very difficult to be accepted in physical and material development. Islam views development with a very feminine perspective. This can be seen from the development in Islam which is not only emphasized on physical development but also non-physical development.